Sex selection drug and congenital malformations in North India - Panda, Chinmayee (International Journal Of Community Medicine And Public Health, 2023)
Background: An increasing incidence of congenital malformations (CMF) has been reported in North India in cases use of traditional drug by Mothers to have male child. Aim was to ascertain the association of Sex selection drug (SSD) and congenital malformations. Methods: This hospital-based age-sex matched pair case control study was done at Advanced Pediatric Centre, Obstretics and Gynaecology department (ANC clinic, Maternity ward, labor room etc.) and Special Clinics, PGIMER, Chandigarh, India in 2019. The mothers were interviewed to collect information about risk factors. Results: Two hundred three CMF (under five children and gestational CMF) cases and same number of controls were studied. Significant association of CMF was observed with the use of sex selection drugs by mothers (OR= 4.35). Conclusions: The use of sex selection drugs is an avoidable risk factor of CMF and is of high public health importance. People need to be educated about this.